Hospital-at-home integrated care programme for older patients with orthopaedic conditions: Early community reintegration maximising physical function. (June 2016) - Mas, Miquel Àngel; Closa, Conxita; Santaeugènia, Sebastià J.; Inzitari, Marco; Ribera, Aida; Gallofré, Miquel
Highlights: Older citizens with orthopaedic conditions are at high risk of permanent disability. We present an innovative programme for the care of vulnerable older patients at home. Patients attending the hospital-at-home unit had good functional outcomes. Under the programme, patients with a hip fracture recover their physical function sooner than those receiving usual care. Abstract: Objective: Older citizens with orthopaedic conditions need specialised care for the facilitation of early community reintegration and restitution of physical function. We introduced a new community care programme as an alternative to usual hospital rehabilitation for orthopaedic patients. Study design: This was an observational study of a cohort of older orthopaedic patients attending a hospital-at-home integrated care programme (HHU), compared with a contemporary cohort of users of a geriatric rehabilitation unit (GRU) in the urban area of Badalona, Catalonia, Spain. Main outcomes measures: Functional gain at discharge was measured using the Barthel Index (BI). Other outcomes were: length of intervention (days), rehabilitation efficiency and discharge destination. Results: Over the 2 years of the study we assessed 270 patients (69 at HHU; 201 at GRU). We found no significant differences in baseline characteristics between HHU and GRU groups—mean (IQR) or % age 83 (79–87) vs. 84 (79–88), cognitive impairment 27.5% vs. 24.9%, functional decline 40 (31–48) vs. 43 (32–58). Overall, we found no statistically significant differences between HHU and GRU groups on functional gain: 35 (22–45) vs. 32 (18–46), and discharge home 85.5% vs. 86.1%. Length of intervention was shorter in the HHU group, 43 (32–56) vs. 57 (44–81); p < 0.01, for hip fracture patients. In a multivariate analysis, the adjusted mean difference in rehabilitation efficiency between HHU and GRU groups in the hip fracture subgroup was 0.27 (0.09 to 0.46); p = 0.004. Conclusions: This hospital-at-home service obtained similar clinical results to the usual hospital-based rehabilitation care, and for hip fracture patients attending that service, rehabilitation efficiency was better.